Analyses of the 2022 Nobel Prize in Physiology or Medicine: Paleogenomics. Issue 1 (2nd January 2023) - Sterner, Elizabeth
ABSTRACT: Svante Pääbo, a founding director of the Max-Planck Institute for Evolutionary Anthropology in Leipzig, Germany, was awarded the 2022 Nobel Prize in Physiology or Medicine for his contribution to the development of the field of paleogenomics. His work on sequencing early hominin DNA has led to advancements in extraction and analysis of ancient DNA. The advancement of paleogenomics can further our understanding of modern humans, their ancestors, and human evolution as well as potentially predicting emerging and re-emerging diseases. A bibliometric analysis of Dr. Pääbo's work follows a general overview of ancient DNA analysis.